2012
DOI: 10.1136/acupmed-2011-010064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Symptoms of Anxiety in Women Undergoing in Vitro Fertilisation: A Prospective Randomised Controlled Study

Abstract: Purpose To determine if acupuncture improves symptoms of anxiety in infertile women undergoing in vitro fertilisation (IVF) treatment. Methods A randomised clinical trial was performed in 43 patients undergoing IVF. The patients were randomised into two groups: test group (n=22) and control group (n=21). The anxiety level of each patient was analysed before and after treatment using the Hamilton Anxiety Rating Scale (HAS). Treatment sessions consisted of four weekly sessions. In the test group, needles were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 14 publications
0
70
0
1
Order By: Relevance
“…The most recent systematic review by Shen et al 12 only found evidence of benefit when follicular phase treatment was combined with treatment around ET, and not when timed around ET alone. It is argued that the latter approach, which typically consists of a single treatment before and one after ET (variations of the Paulus protocol 14 ), is insufficient in duration and 'dose' to have any major effect on endometrial receptivity and/or blood flow, and that putative effects on pregnancy rates in this context may be due to inhibition of post-transfer uterine contractions 51 and/or reduction of patient anxiety, 52 both of which may adversely affect pregnancy rates. 53 54 The efficacy of TEAS suggests that penetration of the skin or muscle is not required in order to effect endometrial receptivity and pregnancy rates, and this is supported by experiments on anaesthetised rats, wherein a measurable increase in uterine blood flow was observed during noxious pinching and innocuous brushing of the hind limb and perineum (regions innervated by the sacral segments).…”
mentioning
confidence: 99%
“…The most recent systematic review by Shen et al 12 only found evidence of benefit when follicular phase treatment was combined with treatment around ET, and not when timed around ET alone. It is argued that the latter approach, which typically consists of a single treatment before and one after ET (variations of the Paulus protocol 14 ), is insufficient in duration and 'dose' to have any major effect on endometrial receptivity and/or blood flow, and that putative effects on pregnancy rates in this context may be due to inhibition of post-transfer uterine contractions 51 and/or reduction of patient anxiety, 52 both of which may adversely affect pregnancy rates. 53 54 The efficacy of TEAS suggests that penetration of the skin or muscle is not required in order to effect endometrial receptivity and pregnancy rates, and this is supported by experiments on anaesthetised rats, wherein a measurable increase in uterine blood flow was observed during noxious pinching and innocuous brushing of the hind limb and perineum (regions innervated by the sacral segments).…”
mentioning
confidence: 99%
“…28 Three of the studies assessed the outcome measure from 1 to 6 months after cessation of treatment in an attempt to determine the rate of remission of symptoms. 23,25,28 Three of the studies used only corporal acupuncture, 23,24,27 while one used only auricular acupuncture, 28 and two used both forms of acupuncture. 25,26 …”
Section: General Characteristicsmentioning
confidence: 99%
“…23,[25][26][27] Three studies were conducted in the United States, 23,25,26 and three were conducted outside the United States, with 166 SNIEZEK AND SIDDIQUI one each in Brazil, 27 Canada, 28 and Norway. 24 Two studies only included pregnant women, 25,26 one study only had women with vasomotor menopausal symptoms, 24 one study only had women who were undergoing in vitro fertilization (IVF), 27 and one study only had patients enrolled in a substance-abuse recovery program. 28 Five of the six studies used acupuncture as the sole treatment in the study arm, while one study used acupuncture as an adjunct with counseling and psychotherapy.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture is a traditional Chinese treatment, widely practiced and now also accepted in the western world for the treatment of obstetric and gynecologic or infertile issues [3]- [6].…”
Section: Introductionmentioning
confidence: 99%